(untitled) (Ameghiniana, 2014)
The lower part of the Trapiche Formation exposed along the western flank of the cerro Potrerillo has yielded a brachiopod assemblage including Trematis sp., Destombesium argentinun n. sp., Reuschella sp. and Rhvnchotrema sp. According to the asssociated conodonts these levels are late Caradocian in age. The uppermost brachiopod assemblage recovered in the río Gualcamayo section is characterized by the new species Trucizetina cnanarensis. These levels are regarded as late Ashgillian in age based on the associated trilobites and the stratigraphic range of Trucizetina. The record of Destombesium and Trucizeiina in the Trapiche Formation suggests a strong faunal connection between the Precordilleran and Mediterranean brachiopod faunas.